ATUR INTERVAL KEHAMILAN UNTUK KELAHIRAN BAYI SEHAT - Dita Sulistyowati, Bety; Mawarti, Retno (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background : Causes of neonatal deaths aged 0-7 days was highest preterm birth and low birth weight that is equal to 35% . Several studies have shown that the interval of pregnancy can be a cause of low birth weight babies, especially in the short interval that is <2 years or the length of the interval> 4 years). Objective : Knowing the relationship with the incidence of pregnancy intervals of low birth weight babies (LBWB) in hospitals Panembahan Senopati Bantul in 2011 . Method : This methods was an observational study with cross-sectional survey. The collection of samples was done by using purposive sampling with a sample of as many as 66 post partum mothers who gave birth more than once. How to use data collection instruments observation sheet. Analysis of the data used is the analysis bivariable univariabel and analysis using Chi-square test with a significance level of p <0.05. Contingency coefficient 0.251 indicates that the close relationship between the interval of pregnancy with a low incidence of LBW . Results : Based on the results of the study interval-risk pregnancies occur LBW 43.9% and very low birth weight infants19.7%. Interval pregnancies at risk of low birth weight by 33.3% and very low birth weight infants 3.0%. The results of Chi-Square test analysis obtained significance value p-value is 0.035 (p <0.05) and the value of contingency coefficient of 0.251 indicates a low relationship closeness. Conclusion : There is a significant relationship between the incidence of pregnancy interval low birth weight babies (LBWB) in hospitals Panembahan Senopati Bantul in 2011. For mothers who are prepared to pay attention to pregnancy and pregnancy interval ANC checks on a regular basis so that no babies born with LBW B. Keywords : Interval Pregnancy, Low Birth Weight Babies (LBW B)